A proposed model to estimate shear contribution of FRP in strengthened RC beams in terms of Adaptive Neuro-Fuzzy Inference System. (15th June 2017) - Naderpour, H.; Alavi, S.A.
Abstract: This study provides a fuzzy-based model for predicting the shear contribution of FRP in RC beams strengthened by externally bonded FRP sheets. For this purpose, ultimate strain of FRP, effective depth of FRP, compressive strength of concrete, width and spacing and angle of FRP, shear span to depth ratio, the elastic modulus of FRP and thickness of FRP were considered as input parameters while shear strength of FRP is treated as the target one. After a comprehensive review in existing literature, 89 FRP-strengthened RC beams were selected which had experienced FRP rupture failure mode. The results indicate that the proposed fuzzy-based model could predict the shear contribution of FRP in RC beams strengthened by FRP sheets with a good degree of precision compared with the results obtained directly from the existing guideline equations such as fib-TG9.3, CIDAR, ACI 440.2R-08 and CSA-S806(12). Proposed model provide an accurate and reliable tool than the guidelines equations.